PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA BERBASIS PENDEKATAN SAINTIFIK UNTUK MENUNTASKAN HASIL BELAJAR SISWA POKOK BAHASAN SISTEM GERAK MANUSIA DI SMP - Netty M Arumisore; Sifak Indana; Soetjipto Soetjipto (Universitas Negeri Surabaya, 2018)
The objective of this research is produce science learning tools that eligible for the completeness of learning outcome students at subject human motion system on the junior high school. The development of this learning tools is based on 3-D model by using test based on One Group Pretest-Posttest Design. The test is conducted on eighth grade student of SMP Negeri Rasiei Teluk Wondama district-Papua Barat. The research consisted of two stages which is: 1) Developing the learning tools consisted of lesson plan, students book, and students worksheet, learning achievement test validated by experts. 2) the lesson learning tools which has been validated by expert is a tested. The instrumental used including observational sheet of students activity, and students response questionnaire. He result of the research shows that: 1) the learning tools is valid; 2) the lesson plan accoplishment is categorized as good; 3) the students activities indicate tha they learn to actively build their own knowledge through a scientific approach; 4) the students responded positively to the learning process; 5) the students learning outcomes of attitude, knowledge, and skill aspects is accomplished. Based on the following results can be concluded that the science learning tools based scientific approach on human motion system is a valid, practical, and effective. Thus the science learning tools can be used on the learning process and proofed to be effective for the completeness of students learning outcome